A Weight Index for the Standardized Uptake Value in 2-Deoxy-2-[F-18]fluoro-d-glucose-Positron Emission Tomography - Thie, Joseph A.; Hubner, Karl F.; Isidoro, Francis P.; Smith, Gary T. (Molecular imaging and biology, 2007)
Known errors in the standardized uptake value (SUV) caused by variations in subject weights W encountered can be corrected by lean body mass or body surface area (bsa) algorithms replacing W in calculations. However this is infrequently done. The aims of the work here are: quantify sensitivity to W, encourage SUV correction with an approach minimally differing from tradition, and show what improvements in the SUV coefficient of variation (cv) for a population can be expected. Selected for analyses were 2-deoxy-2-[F-18]fluoro-D-glucose (FDG) SUV data from positron emission tomography (PET) and PET/computed tomography (CT) scans at the University of Tennessee as well as from the literature. A weight sensitivity index was defined as -n=slope of ln(SUV/W) vs. lnW. The portion of the SUV variability due to this trend is removed by using the defined [formula: see text], or a virtually equal SUVm using [formula: see text], with Q and ID being tissue specific-activity and injected dose. [formula: see text] measures performance. Adapting to animal studies' tradition, [formula: see text] is preferred over the conventional [formula: see text]. For FDG in adults [formula: see text] from averaging over most tissues. In children, however, [formula: see text]. Tissues have the same index if their influx constants are independent of W. Suggested, therefore, is a very simplified [formula: see text], which is dimensionless and keeps the same population averages as traditional SUVs. It achieves [formula: see text]. Hence, for cv's of SUVs below approximately 1/3 improvements over tradition are possible, leading to F's<0.95. Accounting additionally for height, as in SUVbsa, gives very little improvement over the simplified approach here and gives essentially the same F's as SUVm. Introduced here is a weight index useful in reducing variability and further understanding the SUV. Addressing weight sensitivity is appropriate where the cv of the SUVs is below about 1/3. Proposed is the very simple approach of using an average of an adult patient's weight and approximately 70 kg for FDG SUV calculations. Unlike other approaches the dimensionless population average of SUVms is unchanged from tradition.